HARDWARE IN THE LOOP SIMULATION OF HYDROGEN FUEL CELL HYBRID ENERGY MANAGEMENT - Fajri Syahbana, Dwiky
The use of conventional fuels, especially in the field of transportation, is one of the biggest contributors to carbon dioxide. Hydrogen fuel cell is an alternative and environmentally friendly energy source. In the use of hydrogen fuel cells for transportation, several studies have carried out a combination of fuel cells with batteries and supercapacitors because fuel cells have slow dynamics. Batteries and supercapacitors can be used when responding to load changes faster, while supercapacitors is the fastest. Combinations with batteries and supercapacitors can also be used for regenerative braking functions. In combining the three sources, certain configurations are arranged, namely that each source is connected to a DC-DC converter while the output is connected in parallel to the DC bus to supply the load. Batteries and supercapacitors use twoway converters to operate regenerative braking. To maintain fuel cells, batteries, and super capacitors working under a safe working area, a filter-based energy source management system, DC voltage bus control, and predictive model control are designed to produce an optimal converter switching signal that minimize the switching losses. The system designed has been simulated in MATLAB / Simulink, then tested by implementing it in hardware in the loop simulation (HILS). The HILS consists of a simulator of energy sources that run on the PC as well as energy management and MPC on Raspberry Pi hardware. It shows the ability to manage source flows and track DC bus voltages. The effect of adding the MPC horizon in this system is that it can reduce current ripples so that it can reduce converter switching losses. With a prediction horizon of 5, current ripples represented by current-to-peak currents can be reduced to 3.52 A.